Digestibility of different sources and particle sizes of calcium in diets for laying hens during the laying phase - Loirana Lehmkuhl da Rosa Rodrigues; Lays Mayara de Oliveira Ferreira; Marcelo Suzuki Suyama; Clóvis Eliseu Gewehr (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the digestibility of different calcium sources and particle sizes in diets for commercial laying hens during the laying phase. Ninety-five Hisex Brown hens, with 26 weeks of age, were used, distributed in a completely randomized experimental design, in a 3x2 factorial arrangement with three Ca sources (oyster shell meal and the Furquim and Supercal commercial calcitic limestones) and two particle sizes (fine and coarse). The following eight experimental diets were prepared: six in which corn starch was replaced with the evaluated Ca sources and particle sizes; one without Ca; and a basal diet. The Ca digestibility coefficients were similar between the diets containing Furquim limestone and oyster shell meal, which presented greater values than the diets containing Supercal limestone. The results of the in vitro solubility of the Ca particle sizes indicated a relationship between particle size and solubility, where in vitro solubility decreases with the increase in particle diameter. The coarse particle size significantly reduced the digestibility coefficients of the feed and Ca sources analyzed. Oyster shell meal and Furquim calcitic limestone are equivalent sources in terms of the Ca digestibility coefficient, and the use of fine particles increases the digestibility coefficients of the feed and Ca sources.